Estudio de prefactibilidad para la instalación de una planta de producción de agua de mesa alcalina ionizada - Ascue Lazo, André Johai (2020)
In order to determine the feasibility of the project, four relevant criteria were taken into account: market, location, technology and finance. Regarding the market, the demand that was calculated for the first year of the project was 1,261,753 bottles of 625 ml alkaline water (equivalent to 84,116 packs of 15 bottles of 625 ml) at a unit price of S /. 1.60. This price is offered to wholesale distributors, who will then do their own management to sell the product to final consumers. The suggested retail price for the consumer is S / 2.00. For the location, several factors were taken into account in the selection such as availability of raw material, proximity to the target market, availability of workforce, availability of land and transport systems. After an exhaustive analysis for each factor, it was concluded that the most suitable place was Lurin. Regarding technology, there are no limitations for the present project, since both machinery and equipment belonging to the process can be acquired easily. On the other hand, the process that represents the main bottle neck is ionization, with a production capacity of 1,693,037 bottles per year. Finally, from the financial point of view, the total initial investment of the project is S/ 2,652,831.90 and is divided into 70% shareholder’s capital (S/ 1,856,982) and 30% bank financing (S/ 795,849). For this, the financing granted in the market of small and medium companies was investigated; and a loan was obtained with the Banco de Crédito del Perú with an annual effective rate of 15%.